Non-stenotic Carotid Plaques in Embolic Stroke of Unknown Source - Kamtchum-Tatuene, Joseph; Nomani, Ali Z.; Falcione, Sarina; Munsterman, Danielle; Sykes, Gina; Joy, Twinkle; Spronk, Elena; Vargas, Maria Isabel; Jickling, Glen C. (Frontiers in Neurology, 2021)
Embolic stroke of unknown source (ESUS) represents one in five ischemic strokes. Ipsilateral nonstenotic carotid plaques are identified in 40% of all ESUS. In this narrative review, we summarize the evidence supporting the potential causal relationship between ESUS and nonstenotic carotid plaques; discuss the remaining challenges in establishing the causal link between nonstenotic plaques and ESUS, and describe some biomarkers of potential interest for future research. In support of the causal relationship between ESUS and nonstenotic carotid plaque, studies have shown that plaques with high-risk features are 5 times more prevalent in the ipsilateral versus the contralateral carotid and there is a lower incidence of atrial fibrillation during follow-up in patients with ipsilateral nonstenotic carotid plaques. However, nonstenotic carotid plaque with or without high-risk features often coexists with other potential etiologies of stroke, notably atrial fibrillation (8.5%), intracranial atherosclerosis (8.4%), patent foramen ovale (5-9%), and atrial cardiopathy (2.4%). Such puzzling clinical associations make it challenging to confirm the causal link between nonstenotic plaques and ESUS. Several ongoing studies explore whether select protein and RNA biomarkers of plaque progression or vulnerability could facilitate the reclassification of some ESUS as large vessel strokes or help to optimize secondary prevention strategies.